2020
DOI: 10.1111/eje.12498
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of attitudes towards persons with dementia, knowledge of dementia and ageism amongst students in Taiwan and Japan: A cross‐sectional study

Abstract: Introduction:This study aimed to compare the attitudes towards people with dementia, knowledge of dementia and ageism amongst Taiwanese and Japanese dental hygiene students. Material and Methods:A total of 328 students participated in this cross-sectional study. Attitudes, knowledge and ageism were assessed using self-reports.Participants' association with older adults or persons with dementia was also assessed. Primary outcomes included attitude, knowledge and ageism amongst students. Secondary outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, the public in China exhibits negative attitudes towards people diagnosed with dementia. These attitudes are linked to ageism and the fear of the behavioural and psychological symptoms of dementia, which suggest that people diagnosed with dementia deviate from norms (Akifusa et al, 2020).…”
Section: Physical Restraint Use In Home Carementioning
confidence: 99%
See 1 more Smart Citation
“…However, the public in China exhibits negative attitudes towards people diagnosed with dementia. These attitudes are linked to ageism and the fear of the behavioural and psychological symptoms of dementia, which suggest that people diagnosed with dementia deviate from norms (Akifusa et al, 2020).…”
Section: Physical Restraint Use In Home Carementioning
confidence: 99%
“…However, the public in China exhibits negative attitudes towards people diagnosed with dementia. These attitudes are linked to ageism and the fear of the behavioural and psychological symptoms of dementia, which suggest that people diagnosed with dementia deviate from norms (Akifusa et al, 2020). Tension emerges between Confucian culture and the negative social discourse and belief systems held by the public in regard to the value of people living with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Ageism not only hurts older people's identities and quality of life but also causes separation and conflict between generations, impairing social cohesion [ 3 ]. Negative attitudes about older people among nursing undergraduates' fuel ageism and how they perceive older people with dementia [ 4 ]. Age discrimination among nursing students affected social distance for older adults with dementia [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that ageism has a strong relationship with attitudes toward dementia, suggesting that PCC and compassion impact attitudes toward dementia [ [3] , [4] , [5] , [6] , [7] , [9] , [10] , [11] , [12] ]. However, to the authors' knowledge, no study has confirmed how PCC and compassion mediate the relationship between nursing students’ ageism and attitudes toward dementia.…”
Section: Introductionmentioning
confidence: 99%